The impact of authoritarian leadership on workplace bullying from the perspective of Chinese Confucian culture: a mediating model with gender as a moderator - Yang, Junjie; Luo, Ziyi; Yang, Yunxuan; Feng, Hanlin (Frontiers in Sociology, 2025)
Workplace bullying severely impairs employees’ physical and mental health and disrupts the workplace ecosystem. Pinpointing its causes accurately is crucial for effective governance. Drawing on the values of hierarchical order and male dominance over females highlighted in Chinese Confucian culture, and the theoretical framework of the interaction between individuals, environment and behavior (Triadic Reciprocal Determinism), this study takes the hostile work environment as the mediating variable and gender as the moderating variable to explore the influence mechanism of authoritarian leadership on workplace bullying. Data from 1,193 employees were collected through questionnaires, and statistical analyses were conducted using SPSS 29.0 and AMOS software. The results show that authoritarian leadership has a significant positive impact on the occurrence of workplace bullying, and the hostile work environment plays a partial mediating role between them. Meanwhile, compared with men, women are more likely to be targeted by bullying in a hostile environment. This research reveals the profound influence of the concepts of hierarchical order and gender differences in Confucian culture on workplace bullying, and points out the importance of optimizing leadership styles, improving the organizational atmosphere, and paying attention to the vulnerable workplace situation of women in preventing and controlling workplace bullying. The findings provide a theoretical framework for understanding the cultural specificity of workplace behavior and offer gender-differentiated intervention strategies for enterprise management and government policy formulation.